The role of non-coding RNAs in muscle aging: regulatory mechanisms and therapeutic potential - Shin, Yeo Jin; Kwon, Ki-Sun; Suh, Yousin; Lee, Kwang-Pyo (Frontiers in Molecular Biosciences, 2024)
Muscle aging is a complex physiological process that leads to the progressive decline in muscle mass and function, contributing to debilitating conditions in the elderly such as sarcopenia. In recent years, non-coding RNAs (ncRNAs) have been increasingly recognized as major regulators of muscle aging and related cellular processes. Here, we comprehensively review the emerging role of ncRNAs, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), in the regulation of muscle aging. We also discuss how targeting these ncRNAs can be explored for the development of novel interventions to combat age-related muscle decline. The insights provided in this review offer a promising avenue for future research and therapeutic strategies aimed at improving muscle health during aging.